PENGARUH PENAMBAHAN TEPUNG KENTANG TERHADAP SIFAT ORGANOLEPTIK BUMBU GADO-GADO - Langit, Ikhlasul Putri Sekar; Mariana, Rina Rifqie; Issutarti, Issutarti (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2023)
The making of gado-gado seasoning by adding potato flour is expected to get a better texture of the gado-gado seasoning. Production of potato starch has been widely marketed and easy to obtain. This study aims to examine the organoleptic properties of the gado-gado seasoning substituted with potato flour. The type of research used is experimental research. The design in this study used a completely randomized design (CRD) with one treatment, namely the addition of potato flour with three percentages (15%, 25%,35%). The data obtained were then analyzed by the ANOVA method if there was a difference followed by Duncan's test. There are significant differences in the hedonic quality of color, aroma, taste and texture as well as the level of preference for color, aroma, taste and texture. The highest average hedonic quality and level of color preference is found in the addition of 15%, the highest average hedonic quality and aroma preference level is found in the addition of 15%, the highest average hedonic quality and taste preference level is found in the addition of 15%, the highest average hedonic quality and texture preference level found in 15% increments.